IMPACT OF ONLINE LEARNING DURING THE COVID-19 PANDEMIC ON LEARNING ACTIVITIES (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2022)
This research describes whether the social presence can be obtained from online learning of distance education setting. Data in this study employed questionnaire adapted from Rovai (2002) which identified 3 aspects of social presence, namely connectedness aspect, learning aspect, and socio-emotional aspect. Data was taken from 70 students who participated in an 8-weeks online learning. The results showed that all aspects have positive attitudes from students’ point of views. The students experienced connectedness aspect, learning aspect, and socio-emotional aspect in online learning regardless the learning situation which was mostly text-based setting. Keywords: COI Framework, community of inquiry, online learning,